Cardiovascular disease onset in old people with severe hypercholesterolemia. (January 2023) - Coutinho, Elaine R.; Miname, Marcio H.; Rocha, Viviane Z.; Bittencourt, Marcio S.; Jannes, Cinthia E.; Krieger, Jose E.; Pereira, Alexandre C.; Santos, Raul D.
Abstract: Background and aims: Familial hypercholesterolemia (FH) variants are associated with higher atherosclerotic cardiovascular disease risk (ASCVD) even when compared with other forms of severe hypercholesterolemia, especially in young people. Lipid lowering therapies (LLT) may change hypercholesterolemia natural history. This study aimed at evaluating factors associated with occurrence of ASCVD in old severe hypercholesterolemics diagnosed or not with FH and undergoing LLT. Methods: Hypercholesterolemic individuals ≥60 years participating on a genetic cascade screening for FH were divided in 4 groups (2 × 2) according to the presence (variant+) or not (variant-) of FH genetic variants and previous ASCVD (ASCVD+ and ASCVD-). Biomarkers associated with new incident ASCVD events were tested using Cox models. Continuous data shown as medians (%25; %75). Results: From 4, 111 genotyped individuals, 377 (9.1%) were elderly [age 66 (63; 71) years], 28.9% males, 42.7% variant+, 32.1% with previous ASCVD, LLT duration 9 (5; 16) years, and on treatment LDL-cholesterol 144 (109; 200) mg/dL. After 4.8 (7; 3) years of follow up there were 47 incident events (12.4%, 2.7% patient/year). The annualized event rates were 0.8% (95% CI 0.36%; 1.70%), 2.3% (95% CI 1.3%; 4.1%), 5.2% (95% CI 2.8%; 9.7%) and 6.3% (95% CI 4.0%; 10.0%) respectively for groups variant-/ASCVD-, variant+/ASCVD-, variant-/ASCVD+ and, variant+/ASCVD+ (p log rank p < 0.001). Only presence of previous ASCVD was independently associated with incident ASCVD [hazard ratio 3.236 (95%CI 1.497–6.993, p = 0.003)]. No interaction was found for previous ASCVD and variants. Conclusions: In old severe hypercholesterolemic individuals undergoing long-term LLT previous ASCVD was associated with incident events while FH causing variants were not. Graphical abstract: Image 1 Highlights: Familial hypercholesterolemia (FH) genetic variants are implicated in higher atherosclerotic cardiovascular disease risk (ASCVD) risk even in severe hypercholesterolemia. Risk is greater in young people. Lipid lowering therapy may change natural history of hypercholesterolemia in old people. In old severe hypercholesterolemic patients, FH variants were not associated with new ASCVD disease onset. Previous cardiovascular disease was independently associated with new ASCVD onset.